Varieties and similarities of platform capitalisms: a comparative approach of labor regulation in Brazil, Portugal and Spain - Soeiro, José; Seto, Kenzo Soares; Riesgo Gómez, Víctor (Frontiers in Sociology, 2025)
Digital platforms have led to the emergence of a new digital proletariat worldwide, subject to institutional arrangements that put the labor framework outside of labor law. However, this process of remercantilisation and informalisation of work has been accompanied by a transnational tug-of-war over the legal status of these workers. Using a comparative case study approach, this article seeks to describe and problematise the conflict surrounding the regulation of on-location platform work in Brazil, Portugal, and Spain. It looks at (i) the installation process and extension of the activity of on-location platforms in each country; (ii) the political, regulatory, and jurisprudential debate around the socio-legal framework of couriers and drivers, the role of intermediaries, and law-enforcement; (iii) the positions of the different collective actors and political agents (workers organizations, business lobbying, governments) on regulatory models; (iv) the alternative solutions put forward by movements and public policies, namely cooperative or ethically based platforms and their influence on the final model established in each country. The comparison between Brazil, Portugal, and Spain highlights how different national contexts – in terms of collective actors, labor and political institutions, and regulatory processes – regionally shape the global phenomenon of platform capitalism.